2016
DOI: 10.4191/kcers.2016.53.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Glaze Development with Application of Unity Molecular Formula

Abstract: Effects of compositions and sintering conditions on glaze properties are shown in the diagram constructed by using the unity molecular formula (UMF) method in this study. Glossy characteristics of glaze were clearly differentiated by compositional area in the diagram and sintering process. As alumina and silica contents were increased, texture of the glaze became rough and opaque, akin to having been devitrified or underfired. The correlation between glossiness and surface roughness was found to be non-linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Dissolution of the elements produces a more even and smoother surface. This surface reflected the light better than an un-electropolished sample, which subsequently results in better glossiness [19][20][21] . Several works reported that lower surface roughness commonly created better glossiness.…”
Section: Surface Glossinessmentioning
confidence: 99%
“…Dissolution of the elements produces a more even and smoother surface. This surface reflected the light better than an un-electropolished sample, which subsequently results in better glossiness [19][20][21] . Several works reported that lower surface roughness commonly created better glossiness.…”
Section: Surface Glossinessmentioning
confidence: 99%